Simulated analysis of wheel polygons on vibration responses of locomotive axle boxes - HOU Zhaowen; LIU Yongfeng; TAO Gongquan (机车电传动)
Polygonal wear of wheels has a significant influence on the fatigue life of components in the wheel and rail system, as well as on the ride comfort and operational safety of trains. This paper investigates the vibration responses of locomotive axle boxes to the excitation of wheel polygons. To this end, a rigid-flexible coupling dynamics model was developed by combining multi-body dynamics software and finite element analysis software to simulate the locomotive-track system. This model incorporated the flexibility of bogie frames, wheelsets, sleepers, and rails. The measured vibration acceleration results of locomotive axle box were used to verify this model. This study further examined the effects of ideal harmonics and measured irregular wheel polygons in typical cases on vibration responses of locomotives. The findings show that the amplitude of axle box vibration accelerations increase significantly as the wheel polygon passing frequency approaches the resonant frequency of the wheel-rail system in the P2 mode or the wheelset frequency in its natural mode. The magnitude of axle box vibration accelerations exhibit a positive correlation with the depth of the polygon waveforms, rather than a linear correlation with the order of the wheel polygons. Furthermore, under the excitation of measured irregular wheel polygons, the dominant order of the wheel polygons is identified as the primary influencing factor on the axle box vibration accelerations.